The relationship between systemic immune-inflammation index and length of hospitalization in acute pancreatitis - Yasak, Ibrahim Halil; Yilmaz, Mustafa (Bayrakol Medical Publisher, 2023)
Aim: To determine the relationship of the systemic immune-inflammatory index (SII) in acute pancreatitis (AP) with disease severity and length of stay in hospital.Material and Methods: This retrospective study was conducted in the Emergency Department over a 3-year period. The basic and laboratory data were examined from the electronic patient records system of 100 patients who were hospitalised because of pancreatitis.Results: Evaluation was made of 100 patients, comprising 71 females and 29 males, with mild AP determined in 67 and severe AP in 33. The SII and neutrophil-lymphocyte ratio (NLR) values were determined to be significantly higher in the severe AP group (p=0.001, p=0.014, respectively). A statistically significant correlation was determined between the SII and the Glasgow (Imrie) score (r=0.430, p<0.001). According to the Glasgow (Imrie) criteria, the SII was determined to have sensitivity in the differentiation of severe AP. The SII, C-reactive protein level, and Glasgow (Imrie) criteria were determined to be independent predictors of length of stay in hospital.Discussions: The SII was determined to be effective in predicting disease severity and length of stay in hospital in AP patients.
Keywords: Acute Pancreatitis; Inflammation; Systemic Immune-Inflammation Index; Hospitalization